ANALYSIS OF DENSITY AND CHANGE OF AREA SEAGRASS IN CONSERVATION AREA OF TRIKORA REGENCY OF BINTAN RIAU ISLAND - Yohanne Aprilicia; Musrifin Galib; Zulkifli Zulkifli (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACTSeagrasses are plants adapted to live fully in the marine environment. Seagrass plays an important role in coastal areas due to critical habitat for many kinds of marine animals such as fish, mollusks, crustaceans, echinoderms. This study was conducted from March 2018- May 2018 at the Seagrass Beach Conservation Area of Trikora Regency of Bintan Riau Island which aims to know: the density of each seagrass species and the change of seagrass area based on the mapping in 2006-2018. Sampling is done at three stations, namely Station I residential zone, Station II natural seagrass zone and Station III zone tourist resort. Sampling and measurement of water quality was done by using quadratic transect. The results obtained 8 (eight) seagrass species that was of Cymodoceaserrulata, Enhalusacoroide, Halodulepinifolia, Haloduleuninervis, Halophilaovalis, Syringodiumisotifolium, Thalassiahemprichii, Thalassodendronciliatum. The highest seagrass density obtained at Station II is 487.11 tegakan/m2 in the low seagrass areas. Referring to the criterion of seagrass density according to Braun-Blanquet that seagrass with density> 175 is very tight. The result of the change of seagrass area in 2006-2018 happened addition area of 122 ha, thus there is influence from TRIMANDES (activityTrikoraSeagrass Management Demonstration Site)onseagrass community.Keywords: Seagrass, Density, Area, Trikora